(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The main aim is to produce a new form of connectedness namely Soft Jc Connected. Further more we have introduced Soft Jc Seperated Sets and we have obtained some results using Soft Hyperconnected set. Further we have compared our Soft Jc Connected Space with Soft Connected and Soft Connected spaces. Moreover we have proved Generalization of Intermediate Value Theorem with respect to Soft Jc Connected and we have discussed some properties of Soft Jc Connected Space in detail.